HMGA1 Induces Intestinal Polyposis in Transgenic Mice and Drives Tumor Progression and Stem Cell Properties in Colon Cancer Cells - Belton, Amy; Gabrovsky, Alexander; Bae, Young Kyung; Reeves, Ray; Iacobuzio-Donahue, Christine; Huso, David L.; Resar, Linda M. S. (PLOS ONE, 2012)
Background Although metastatic colon cancer is a leading cause of cancer death worldwide, the molecular mechanisms that enable colon cancer cells to metastasize remain unclear. Emerging evidence suggests that metastatic cells develop by usurping transcriptional networks from embryonic stem (ES) cells to facilitate an epithelial-mesenchymal transition (EMT), invasion, and metastatic progression. Previous studies identified HMGA1 as a key transcription factor enriched in ES cells, colon cancer, and other aggressive tumors, although its role in these settings is poorly understood. Methods/Principal Findings To determine how HMGA1 functions in metastatic colon cancer, we manipulated HMGA1 expression in transgenic mice and colon cancer cells. We discovered that HMGA1 drives proliferative changes, aberrant crypt formation, and intestinal polyposis in transgenic mice. In colon cancer cell lines from poorly differentiated, metastatic tumors, knock-down of HMGA1 blocks anchorage-independent cell growth, migration, invasion, xenograft tumorigenesis and three-dimensional colonosphere formation. Inhibiting HMGA1 expression blocks tumorigenesis at limiting dilutions, consistent with depletion of tumor-initiator cells in the knock-down cells. Knock-down of HMGA1 also inhibits metastatic progression to the liver in vivo. In metastatic colon cancer cells, HMGA1 induces expression of Twist1, a gene involved in embryogenesis, EMT, and tumor progression, while HMGA1 represses E-cadherin, a gene that is down-regulated during EMT and metastatic progression. In addition, HMGA1 is among the most enriched genes in colon cancer compared to normal mucosa. Conclusions Our findings demonstrate for the first time that HMGA1 drives proliferative changes and polyp formation in the intestines of transgenic mice and induces metastatic progression and stem-like properties in colon cancer cells. These findings indicate that HMGA1 is a key regulator, both in metastatic progression and in the maintenance of a stem-like state. Our results also suggest that HMGA1 or downstream pathways could be rational therapeutic targets in metastatic, poorly differentiated colon cancer.